Biliary atresia with splenic malformation with associated ductal plate malformation and duodenal atresia: A case report - Raktim Mukherjee; Aniket Halder; Suman Kumar Das; Suchandra Mukherjee; Uttara Chatterjee (Indian Journal of Pathology and Microbiology)
Biliary atresia (BA) is the most common cause of the obstructive type of neonatal cholestasis that requires prompt surgical intervention. About 10% of neonates with BA have other congenital anomalies, of which splenic malformation (BASM) is a well-known distinct sub-group. There is sparse literature on the association of duodenal atresia and ductal plate malformation (DPM) in patients of BASM. We describe a BASM associated with DPM and duodenal atresia in a 35-day-old infant, who succumbed at 40 days, before portoenterostomy could be performed. Duodenal atresia can be one of the associated malformations associated with BASM and ductal plate abnormalities. In our case, the child did not survive.